2008
DOI: 10.1007/s12011-008-8282-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III) Nanoparticles Affect Hormone and Immune Responses in Heat-Stressed Rats

Abstract: This study was conducted to evaluate the effects of chromium nanoparticles (CrNano) on the hormone and immune responses of rats in heat stress condition. A total of 80 male Sprague-Dawley rats were randomly assigned to four dietary treatment groups (n = 20). The first group was offered a basal diet as a control. The second, third, and fourth groups received basal diet supplemented with 150, 300, and 450 microg/kg Cr, respectively, in the form of CrNano. At the end of the 8-week trial, growth performance, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…On the other hand, lymphocytes significantly increased (p=0.0004) in chicken fed 3000 ppb NanoCrPic, whereas heterophils and heterophil to lymphocyte ratio were significantly decreased in both 500 and 3000 ppb NanoCrPic groups (p<0.05). The results were agreement with those of Zha et al (2008) who found that dietary supplementation of 150, 300, and 450 ppb Cr from NanoCr enhanced the lymphoproliferative response in Sprague-Dawley rats; Toghyani et al (2007) also reported increases in lymphocyte counts and decreases in heterophil to lymphocyte ratios in 1000 and 1500 ppb CrPic supplementation in heat-stressed chicks.…”
Section: The Effects Of Different Levels Of Nanocrpic On Immune Resposupporting
confidence: 91%
“…On the other hand, lymphocytes significantly increased (p=0.0004) in chicken fed 3000 ppb NanoCrPic, whereas heterophils and heterophil to lymphocyte ratio were significantly decreased in both 500 and 3000 ppb NanoCrPic groups (p<0.05). The results were agreement with those of Zha et al (2008) who found that dietary supplementation of 150, 300, and 450 ppb Cr from NanoCr enhanced the lymphoproliferative response in Sprague-Dawley rats; Toghyani et al (2007) also reported increases in lymphocyte counts and decreases in heterophil to lymphocyte ratios in 1000 and 1500 ppb CrPic supplementation in heat-stressed chicks.…”
Section: The Effects Of Different Levels Of Nanocrpic On Immune Resposupporting
confidence: 91%
“…Sirirat et al (2012), in a study conducted to investigate the effects of different levels nanoparticles of chromium picolinate (NanoCrPic) on the performance, immune responses, mineral retention, and tissues accumulation of chickens reported significant increase in lymphocytes (p<0.0004) as the level of Cr supplementation increased to 3000ppb. Zha et al (2008) observed lympho proliferative response in rats feed supplementary Cr of 150, 300 and 450 ppb. In the present study, the increase in the number of WBC counts and WBC sub-groups in treatment groups supplemented with vitamin E, zinc and chromium individually or in combination could be attributed to the increase in immunity arising from the supplemented ingredients due to their antioxidant properties, with the ability to quench free radicals.…”
Section: Effect On Hematological Characteristicsmentioning
confidence: 80%
“…Under heat stress condition, dietary CrPic decreased glucose level in quails (Quiniou et al 2000) and broiler chickens (Samanta et al 2008), indicating improved glucose clearance and insulin sensitivity. Zha et al (2009) indicated that heatstressed male Sprague-Dawley rats fed with nano-Cr had lower insulin. However, supplementation of CrPic linearly increased insulin concentration at levels from 200 to 1200 μg/kg (Sahin et al 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…Farm animals tend to reduce feed intake to adapt to high environment temperature (Nardone et al 2010). Zha et al (2009) suggested that nCrPic can balance circulating cortisol and insulin level to maintain homeostasis. The anorexigenic actions of cortisol can mediated via reducing circulating ghrelin levels as well as GHSR1a-LR (biologically active ghrelin receptor) expression and/or suppressing neuropeptide Y expression (Janzen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation